Lenvatinib enhances antitumor immunity by promoting the infiltration of TCF1+ CD8+ T cells in HCC via blocking VEGFR2. Issue 4 (20th January 2023) - Mei, Zhibin; Gao, Xingxing; Pan, Caixu; Wu, Qinchuan; Wang, Shuai; Qian, Junjie; Xu, Zhentian; Xu, Kangdi; Zhou, Lin; Zhen, Shushen
Abstract: Lenvatinib is the favorable treatment for advanced hepatocellular carcinoma (HCC), and it is currently undergoing phase III clinical trials. However, the specific effects of lenvatinib on PD1 + CD8 + T cells in HCC microenvironment have not been systematically studied. Here, we established an orthotopic hepa1‐6 mouse model treated with lenvatinib to investigate CD8 + T cells' role in the tumor and spleen. We found an increasing proportion of TCF‐1 + in PD1 + CD8 + T cells and proliferation of PD1 + CD8 + T cells after lenvatinib treatment. Meanwhile, lenvatinib treatment upregulated the expression of granzyme B on PD1 + CD8 + T cells both in vitro and in vivo. Lenvatinib activated the endogenous mTOR pathway of exhausted CD8 + T cells, and mTOR pathway blockade eliminated the antitumor effect of lenvatinib and function of PD1 + CD8 + T cells. The effects of the mTOR pathway on PD1 + CD8 + T cells after lenvatinib treatment were mediated by VEGFR2 inhibition. Overall, our work provides insight into the mechanism of lenvatinib's antitumor efficacy through exhausted CD8 + T cells in HCC treatment. Abstract : In this work, we observed TCF1 + PD1 + CD8 + T cells gradually decreased with tumor progression. We discovered that lenvatinib promoted the production of pTex and increased the proportion of the pTex subset in all exhausted CD8 + T cells both in tumor and spleen. At the same time, the proliferation activity of PD1 + CD8 + T cells was significantly increased, and the PD1 + CD8 + T cells secreted more granzyme B, which means greater tumor‐killing function under the influence of lenvatinib. Furthermore, lenvatinib affects PD1 + CD8 + T cell differentiation by affecting the PI3K/Akt/mTOR signaling pathway. After the combination of lenvatinib and rapamycin, the effect of lenvatinib on pTex and granzyme B expression was significantly inhibited. Finally, we found lenvatinib affects the PI3K/Akt/mTOR signaling pathway by blocking VEGFR2. Overall, our work provides insight into the mechanism of lenvatinib's antitumor efficacy through exhausted CD8 + T cells in HCC treatment.